Portal-systemic by-pass and the analysis of survival rate research resultsin patients with liver cirrhosis - F. G. Nazyrov; A. V. Devyatov; R. A. Ibadov (Бюллетень сибирской медицины)
The present research is based on the analysis of 500 patients with liver cirrhosis with complicated portal hypertension. All patients were examined and operated in the department of portal hypertension and pancreatic-duodenal zone surgery of acad. V. Vakhidov Republican Specialized Surgery Centre (Tashkent) during the period of 1976 - January 2007, included. The appreciation of survival rate curve in patients with liver cirrhosis after portal-systemic shunting is given on the basis of the prognosis factors stratification, that predetermines individual approach to each patient in the choice of surgical tactics and rehabilitation actions. We have mostly studied results and efficacy of different variants of portal-systemic shunting in stratificated groups, that allowed to reveal the most favourable group of patients with LC in respect of long-term prognosis after portal-systemic shunting.